Analisis Sedimentasi pada Saluran Drainase Jalan Perjuangan, Medan - rapael_sihite shally_raphael_risky; Raphael Sihite; Rizky Simanjuntak Simanjuntak (Fakultas Teknik Universitas Hamzanwadi, 2026)
Urban drainage systems play an important role in conveying rainwater and preventing flooding. However, their performance often decreases due to sedimentation, land-use changes, and lack of maintenance. This study aims to analyze the condition of drainage channels, calculate sediment volume, and evaluate the impact of sedimentation on channel capacity in Jalan Perjuangan, Medan.The research method used is field survey and data analysis. Measurements were conducted on nine drainage segments, including channel width, depth, water level, and sediment thickness. Runoff discharge was calculated using the rational method, and population projection was analyzed to estimate future drainage loads.The results show that most drainage channels experience sedimentation with varying thickness. Sedimentation reduces the flow cross-sectional area, decreasing channel capacity. Some segments are still in good condition, while others are narrowed due to sediment and waste accumulation. Therefore, periodic maintenance and capacity improvement are necessary to ensure optimal drainage performance.